Frequency of Uterine Scar Dehiscence and Its Associated Risk Factors in Patients with Previous Lower Segment Cesarean Section at Jinnah Post Graduate Medical Center, Karachi - Zahra, Qandeel; Naseeb, Shazia (Indus Journal of Bioscience Research, 2025)
Introduction: Uterine scar dehiscence is a dangerous occurrence in women with previous cesarean sections, as it has the potential to lead to a uterine rupture with poor maternal and fetal outcomes. This is a cross-sectional study to ascertain the prevalence of scar dehiscence and its associated risk factors among women who had previous lower-segment cesarean sections in Jinnah Postgraduate Medical Centre, Karachi. Study setting: The study was conducted at the Department of Obstetrics and Gynecology, Jinnah Postgraduate Medical Centre (JPMC), Karachi between January, 2024 and June, 2024, hence covering a six months period in a test and control group. Objectives: The objective of this study was to review scar dehiscence of the uterus and to suggest possible risk factors in patients undergoing one or more of the lower segment cesarean sections at JPMC, Karachi. Materials and Methods: The study was a cross-sectional study of 277 post operatively cesarean section patients. Data was obtained from chart review, intraoperative note and findings. Data analysis was done using Statistical Package for Social Sciences (SPSS). Results: The prevalence of uterine scar dehiscence was determined to be 6.9%. The important risk factors included trial of labour after cesarean, short inter-pregnancy interval, wound infection. Conclusion: Uterine scar dehiscence is an adverse outcome that depends on a number of causes. Risk management measures and preventive measures play a significant role in management.